Species of the genus Hyadina from China (Diptera: Ephydridae) - Zhang, Junhua; Yang, Ding (Zootaxa, 2009)
The genus Hyadina Haliday is recorded from continental China for the first time. Four species, H. jinpingensis sp. nov., H. longicaudata sp. nov., H. quinquepunctata sp. nov. and H. sauteri Cresson, are described. All the species are distributed in Oriental China. A key to the Chinese species of Hyadina is presented.